Prevalence of insomnia symptoms and the use of benzodiazepines and Z-drugs for their treatment among medical students - Balčiūnaitė , B.; Būgaitė , V.; Karnickas , M. (Neurologijos seminarai, 2020)
Background. Even though it is common for medical students to complain about insomnia symptoms, no study has been conducted in Lithuania to determine the prevalence of insomnia symptoms among medical students. The aim of this study was to determine the prevalence of insomnia symptoms, to evaluate students’ knowledge about benzodiazepine treatment and to examine the means used by students to treat sleep disorders.Materials and methods. From December 2019 to April 2020, 321 medical students from Vilnius University (VU) (138 students) and Lithuanian University of Health Sciences (LUHS) (183 students) participated in an anonymous online survey including 28 multiple choice questions. The acquired data was analysed using Microsoft Excel and the statistical p value of
Keywords: insomnia; benzodiazepines; Z-drugs